A Selected Review of Impacts of Ocean Deoxygenation on Fish and Fisheries - Hongsik Kim; Ana C. Franco; U. Rashid Sumaila (Fishes, 2023)
Oxygen is crucial for the survival of marine species. Yet, the ocean has experienced a loss of approximately 2% of its oxygen inventory since the last century, resulting in adverse impacts on marine life and ecosystems. In particular, changes in the gap between the supply and demand for dissolved oxygen lead to physiological and ecological variations, which cause alterations in habitats and food webs for fish and ecosystem services. These changes vary over time and by region, and the heterogeneous characteristics of marine species bring about non-linear consequences to human society. Despite this, identifying the potential ripple effects of deoxygenation on human society is challenging due to the integrated impacts of other stressors, such as global warming and ocean acidification, and their varying changes depending on environmental conditions and regions, such as upwelling and eutrophication. Therefore, we conducted a literature review on ocean deoxygenation and its effects on fish dynamics and the ecosystem, with a focus on the environmental and societal impact, to present crucial considerations and pathways for future research on ocean deoxygenation. We found that quantitative approaches are necessary to assess the dynamic changes under deoxygenation, and the consequent effects on marine ecosystems should be verified to exploit the natural resources from the ocean. One of the most reliable approaches to quantifying the ripple impacts of deoxygenation is to model spatial and temporal changes with other climate stressors, forming a global network encompassing socio-economic and regional effects of this global change to facilitate and improve capabilities to address the impacts of ocean deoxygenation.